Combined Effect of CYP2C19 Genetic Polymorphisms and C-Reactive Protein on Voriconazole Exposure and Dosing in Immunocompromised Children - Chen, Juan; Wu, Ying; He, Yuelin; Feng, Xiaoqin; Ren, Yuqiong; Liu, Shiting (Frontiers in Pediatrics, 2022)
Background: Pediatric patients have significant interindividual variability in voriconazole exposure. The aim of the study was to identify factors associated with voriconazole concentrations and dose requirements to achieve therapeutic concentrations in pediatric patients. Methods: Medical records of pediatric patients were retrospectively reviewed. Covariates associated with voriconazole plasma concentrations and dose requirements were adjusted by using generalized linear mixed-effect models. Results: A total of 682 voriconazole steady state trough concentrations from 91 Chinese pediatric patients were included. Voriconazole exposure was lower in the CYP2C19 normal metabolizer (NM) group compared to the intermediate metabolizer (IM) group and the poor metabolizer (PM) group(P=0.0016, P＜0.0001). The median daily dose of voriconazole required to achieve therapeutic range demonstrated a significant phenotypic dose effect. The extent of impact of C-reactive protein (CRP) levels on voriconazole trough concentrations and dose requirements varied between CYP2C19 phenotypes. Increases of 20, 120, 245 and 395 mg/L from 5mg/L in CRP levels were associated with increases in voriconazole trough concentration by 22.22%, 50%, 64.81% and 75% respectively in the NM group, by 39.26%, 94.48%, 123.93% and 146.63% respectively in the IM group, and by 17.17%, 37.34%, 46.78% and 53.65% respectively in the PM group. Meanwhile, increases of 20, 120, 245 and 395 mg/L from 5mg/L in CRP levels were associated with increases in voriconazole dose requirements by 7.15%, 14.23%, 17.35%, and 19.43% respectively in the PM group, 3.71%, 7.38%, 8.97% and 10.03% respectively in the NM group, and by 4%, 9.10%, 11.05% and 12.35% respectively in the IM group. In addition, age and presence of immunosuppressants had significant effects on voriconazole exposure. Conclusions: Our study suggested that CYP2C19 phenotypes, CRP concentrations, age, and the presence of immunosuppressants were factors associated with the pharmacokinetic changes in voriconazole. There was heterogeneity in the effect of CRP on voriconazole plasma concentrations across different CYP2C19 genotypes. Combining relevant factors with dose adaptation strategies in TDM may help to reduce the incidence of subtherapeutic and supratherapeutic concentrations in clinical practice.